SEKOLAH SEPAKBOLA DI MAKASSAR - Amrullah, Muhammad Irsan; Wasilah, Wasilah; Marwati, Marwati (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
Football is a sport that uses a ball which is played by two teams, each team consists of 11 (eleven) persons. School football serves as a container or a place of education and training young players in which summarizes various educational activities, among others, the basic tools and techniques that supports football training program in this container. The soccer school students get grinding their talents. South Sulawesi as one of the national football business recognizable enough. Makassar city has a lot of young players with the potential to be developed in order to be able to become a professional player. Moreover Makassar city since Ramang era until modern era none who do not know the figure of the young talents of Makassar, both Indonesian National team in various competitions Internasional. Therefore, we need a way to increase the achievements in Makassar city, one of them is withsetting up a football school. With the football schools, each individuals can be nurtured from an early age so that talented young players can hone his talents by providing good guidance between theory and its application in the field.